Book Review—Anne Applebaum’s Red Famine (2017) - Frank Hordijk (Nordlit: Tidsskrift i litteratur og kultur, 2019)
The theme setting and particular relevance of artificial or man-made famines seems to come up in intervals, when tensions re-arise between ‘Western’ powers and Russia and seems to be useful for the purposes of ‘demonizing’ ‘Putin’—the current President of the Russian Federation, Vladimir Putin (2000–2008; 2012–)—, ‘the Kremlin’, the Russian government; or simply ‘Russia’ in the eyes of ‘the West’. In recent years, the famine of 1932–1933 has reached new heights as a politicized event to be instrumentalized in a ‘memory war’ on many discursive levels (history, mass media, memorialization, etc.) between key-representatives of the current countries Ukraine and Russia (Hordijk 2018). This should, symptomatically, remind us of the sheer power that media narratives have in shaping public imaginations.